1987
DOI: 10.1002/cjce.5450650510
|View full text |Cite
|
Sign up to set email alerts
|

On the determination of kinetic parameters for the regeneration of cracking catalyst

Abstract: In the study of the regeneration of cracking catalyst, two approaches may be taken when determining the kinetic rate constant for the coke combustion reaction. A global coke burning rate equation may be considered, based on the observed oxygen concentration and carbon dioxide to carbon monoxide molar product ratio. This reaction may also be represented by an intrinsic coke burning equation which is a function of the oxygen concentration and the carbon dioxide to carbon monoxide molar ratio at the reaction site… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
13
0

Year Published

1988
1988
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 5 publications
0
13
0
Order By: Relevance
“…As was demonstrated recently by Morley and de Lasa (1987), it can be predicted from theoretical considerations that the value of the coke combustion rate constant is independent of the rate equation chosen for the carbon monoxide oxidation reaction. Thus, the coke burning rate constant, k c , was not affected by the model for homogeneous CO combustion.…”
Section: Resultsmentioning
confidence: 83%
See 2 more Smart Citations
“…As was demonstrated recently by Morley and de Lasa (1987), it can be predicted from theoretical considerations that the value of the coke combustion rate constant is independent of the rate equation chosen for the carbon monoxide oxidation reaction. Thus, the coke burning rate constant, k c , was not affected by the model for homogeneous CO combustion.…”
Section: Resultsmentioning
confidence: 83%
“…The set of equations representing the mass balances of 02, CO and C02 in the catalytic bed is similar to that developed for homogeneous CO oxidation. However, as proposed by Morley and de Lasa (1987), the oxygen mass balance in a microcatalytic reactor containing a weakly promoted catalyst (1 100 p.p.b. of Pr) was modified to include a coke combustion term along with a catalytic CO combustion term.…”
Section: Regeneration Of Cracking Catalystmentioning
confidence: 90%
See 1 more Smart Citation
“…A reaction similar to coke steam gasification is the combustion of coke on the catalyst. This reaction has been extensively studied [25][26][27][28][29]. It has been shown that, in most cases, the kinetics of coke combustion at temperatures of 500-600ºC follow with first order kinetics, even considering over 80% coke removal in less than 5 minutes [25].…”
Section: Kinetics Of Steam Reforming From Tpd Experimentsmentioning
confidence: 99%
“…The earliest models were single-phase, simplecontacting model with plug flow, and dispersion of reacting components with tanks in series (Arthur, 1951;Rowe & Patridge, 1965;Weiz & Godwin, 1966). Several workers (Weiz & Godwin, 1966;Morley & De-Lasa, 1987;Morley & De-Lasa, 1988) carried out extensive studies on the kinetics of coke burning reactions for zeolite catalyst and estimated the kinetic parameters for the process but did not apply the kinetic parameters to simulate industrial FCC regenerator. Other workers (De-Lasa et al, 1981;Errazu et al, 1979;Krishnaiah et al, 2007) performed steady-state analysis of the regenerator using the two-phase theory (bubblephase rich in gases, and emulsion-phase rich in catalyst particles).…”
Section: Introductionmentioning
confidence: 99%